Assessment of a rapid liquid-based cytology method for measuring sputum cell counts - Martin, M.J.; Lee, H.; Meakin, G.; Green, A.; Simms, R.L.; Reynolds, C.; Winters, S.; Shaw, Dominick E.; Soomro, Irshad N.; Harrison, Timothy W. (BMJ Publishing Group, 2016)
Differential sputum cell counting is not widely available despite proven clinical utility in the management of asthma. We compared eosinophil counts obtained using liquid-based cytology (LBC), a routine histopathological processing method, and the current standard method. Eosinophil counts obtained using LBC were a strong predictor of sputum eosinophilia (≥3%) determined by the standard method suggesting LBC could be used in the management of asthma.